Aplikasi Perencanaan Perkerasan Runway Menggunakan Software Faarfield - Viktor Suryan; M Rafli Fazal; Suci Risky Nur Afriyani; Virma Septiani; Anggi Nidya Sari; Siti Fatimah; Linda Winiasri (Jurnal Talenta Sipil, 2023)
One of the facilities that support air transportation is the airport. The airport functions as a node for aircraft movements, passengers are one of the important infrastructures that can be expected to accelerate the improvement of the community's economy. The runway is one of the important infrastructure in the airport. This study aims to plan the pavement thickness at Minangkabau International Airport for up to 20 years. The study used the FAA method, namely the FAARFIELD application. With a growth rate of passengers and aircraft movements of 4-10%, the resulting pavement thickness for the runway is 141.28 cm with a thickness of 15 for each surface, base and subbase course; 36.93; 89.34 cm. while for the taxiway pavement on the surface course it is divided into critical and non-critical areas of 8 and 5 cm.